Propuesta de automatización para u proceso de envasado y sellado de yogurt. - Caisaguano Quillupangui, Diego Wladimir (2021)
Automation in the industry is growing, since it allows to control and monitor processes automatically, and therefore, reducing human work, at present, small dairy farms do not have an automatic process in any sector of the plant. This is why the present degree project is about a proposal of automation for a process of packaging and sealing of yogurt, in the company Lácteos Verito of the Parish of Alóag province of Pichincha, This proposal will allow the owner to observe the operation of the packaging and sealing process automatically in the 500 ml, 1 litre, 2 litre and 3 different flavours containers, by means of the communication of the Unity 3D platform and the Oculus Rift glasses. You will enter an immersive virtual environment, where you will feel like you are inside the production plant in real time, in addition to being able to manipulate the variables (amount of packaging, size, taste, etc.) the packaging and sealing process can be started by choosing the taste and size of the packaging The mathematical model of the transfer function and the tuning method of COHEN COON are used for correct operation, through the link of the instrumentation software such as LabVIEW with that of the Unity graphic engine.